Glucose-Derived Raspberry Ketone Produced via Engineered Escherichia coli Metabolism - Masuo, Shunsuke; Saga, Chisa; Usui, Kurumi; Sasakura, Yuma; Kawasaki, Yukie; Takaya, Naoki (Frontiers in Bioengineering and Biotechnology, 2022)
The demand for raspberry ketone (RK) as a plant-based natural flavoring agent is high, but natural RK is one of the most expensive flavor compounds due to its limited content in plants. Here, we produced RK de novo from simple carbon sources in Escherichia coli. We genetically engineered E. coli metabolism to overproduce the metabolic precursors tyrosine and p-coumaric acid and increase RK production. The engineered E. coli produced 19.3- and 1.9 g/L of tyrosine and p-coumaric acid from glucose, respectively. The p-coumaric acid CoA ligase from Agrobacterium tumefaciens and amino acid substituted benzalacetone synthase of Rhemu palmatum (Chinese rhubarb) were overexpressed in E. coli overproducing p-coumaric acid. The overexpression of fabF, encoding β-ketoacyl-acyl carrier protein synthetase II increased intracellular malonyl-CoA, the precursor of benzalacetone synthase for RK biosynthesis, and improved RK production. Fed-batch cultures given glucose as a carbon source produced 62 mg/L of RK under optimized conditions. Our production system is inexpensive and does not rely on plant extraction; thus, it should significantly contribute to the flavor and fragrance industries.